Glyphosate infiltrates the brain and increases pro-inflammatory cytokine TNFα: implications for neurodegenerative disorders - Joanna K. Winstone; Khyatiben V. Pathak; Wendy Winslow; Ignazio S. Piras; Jennifer White; Ritin Sharma; Matthew J. Huentelman; Patrick Pirrotte; Ramon Velazquez (Journal of Neuroinflammation, 2022)
Abstract Background Herbicides are environmental contaminants that have gained much attention due to the potential hazards they pose to human health. Glyphosate, the active ingredient in many commercial herbicides, is the most heavily applied herbicide worldwide. The recent rise in glyphosate application to corn and soy crops correlates positively with increased death rates due to Alzheimer’s disease and other neurodegenerative disorders. Glyphosate has been shown to cross the blood–brain barrier in in vitro models, but has yet to be verified in vivo. Additionally, reports have shown that glyphosate exposure increases pro-inflammatory cytokines in blood plasma, particularly TNFα. Methods Here, we examined whether glyphosate infiltrates the brain and elevates TNFα levels in 4-month-old C57BL/6J mice. Mice received either 125, 250, or 500 mg/kg/day of glyphosate, or a vehicle via oral gavage for 14 days. Urine, plasma, and brain samples were collected on the final day of dosing for analysis via UPLC–MS and ELISAs. Primary cortical neurons were derived from amyloidogenic APP/PS1 pups to evaluate in vitro changes in Aβ40-42 burden and cytotoxicity. RNA sequencing was performed on C57BL/6J brain samples to determine changes in the transcriptome. Results Our analysis revealed that glyphosate infiltrated the brain in a dose-dependent manner and upregulated TNFα in both plasma and brain tissue post-exposure. Notably, glyphosate measures correlated positively with TNFα levels. Glyphosate exposure in APP/PS1 primary cortical neurons increases levels of soluble Aβ40-42 and cytotoxicity. RNAseq revealed over 200 differentially expressed genes in a dose-dependent manner and cell-type-specific deconvolution analysis showed enrichment of key biological processes in oligodendrocytes including myelination, axon ensheathment, glial cell development, and oligodendrocyte development. Conclusions Collectively, these results show for the first time that glyphosate infiltrates the brain, elevates both the expression of TNFα and soluble Aβ, and disrupts the transcriptome in a dose-dependent manner, suggesting that exposure to this herbicide may have detrimental outcomes regarding the health of the general population.